1999
DOI: 10.1007/bf02475746
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the acidic properties by introduction of zinc into ZSM-5 zeolites

Abstract: Abs~aetAromatization of n-hexane and disproportionation of toluene over H-ZSM-5 and Zn-ZSM-5 prepared by ion-exchange with aqueous solution has been studied.Introduction of zinc into ZSM-5 does not si~ificantly affect the total acidity determined by TPDA, but causes redistribution in the strength and type of acid sites. From the results it was concluded that the first step in the aromatization of n-hexane on Zn-ZSM-5 is probably the formation of carbonium ions by hydride abstraction with acid sites in zeolite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The observed decrease in the activity of the mechanical mixture in comparison with the pure acid form can be an indirect evidence that the concentration of proton sites in the mechanical mixtures decreases. This can be supposed on the basis of the results reported in our previous work 10 , where it was shown that increasing the ion-exchange degree the conversion of toluene in ion-exchanged Zn-ZSM-5 samples continuously decreases. In addition on the basis of FTIR measurements using into cationic positions of ZSM-5 zeolites causes decrease in the concentration of proton sites in the catalyst and generation of new, relatively strong Lewis acid sites 9 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The observed decrease in the activity of the mechanical mixture in comparison with the pure acid form can be an indirect evidence that the concentration of proton sites in the mechanical mixtures decreases. This can be supposed on the basis of the results reported in our previous work 10 , where it was shown that increasing the ion-exchange degree the conversion of toluene in ion-exchanged Zn-ZSM-5 samples continuously decreases. In addition on the basis of FTIR measurements using into cationic positions of ZSM-5 zeolites causes decrease in the concentration of proton sites in the catalyst and generation of new, relatively strong Lewis acid sites 9 .…”
Section: Resultsmentioning
confidence: 82%
“…By temperature-programmed desorption of ammonia (TPDA) it was also shown that with increasing amount of zinc in cationic positions, the amount of ammonia desorbed above 450°C increases and the n-hexane conversion at 420°C continuously increases with simultaneous increase in the selectivity to aromatics. In addition, it was shown that the toluene conversion continuously decreases with increasing amount of zinc in cationic positions, indicating a decrease in the concentration of Brønsted acid sites in the zeolite 10 .…”
mentioning
confidence: 98%
“…The experimental evidence suggests that both zinc and gallium species are either directly or indirectly responsible for increasing the rate of dehydrogenation of the alkane reactant 5. One proposal is that hydride abstraction in the vicinity of Ga 6 and Zn 7 sites is the initial rate‐determining step. Others have concluded that Zn and Ga cations are the driving force for dehydrogenation by combining the H‐atoms, which form during the activation of CH at Bronsted acid sites 8.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs by the cyclic reduction and oxidation of Zn and Ga species 9. All other reaction steps occur on Bronsted acid sites within the zeolite micropores, 5 although it has been suggested that zinc may also be involved in oligomerization of the alkenium ions and dehydrogenation of cycloalkenes 7.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction products can be accounted for by the following monomolecular cracking for n-hexane: [15] Variation in mol% of species in gas fraction versus (b) Fig.3 Variation of compounds concentration in gas fraction versus temperature for Ce/H-ZSM-5 catalyst in (a) nitrogen or (b) hydrogen carrier gas, % mol…”
Section: Resultsmentioning
confidence: 99%